Vegetation Index Methods for Estimating Evapotranspiration by Remote Sensing - Glenn, E. P.; Nagler, P. L.; Huete, A. R. (Surveys in Geophysics, 2010)
Evapotranspiration (ET) is the largest term after precipitation in terrestrial water budgets. Accurate estimates of ET are needed for numerous agricultural and natural resource management tasks and to project changes in hydrological cycles due to potential climate change. We explore recent methods that combine vegetation indices (VI) from satellites with ground measurements of actual ET (ET(a)) and meteorological data to project ET(a) over a wide range of biome types and scales of measurement, from local to global estimates. The majority of these use time-series imagery from the Moderate Resolution Imaging Spectrometer on the Terra satellite to project ET over seasons and years. The review explores the theoretical basis for the methods, the types of ancillary data needed, and their accuracy and limitations. Coefficients of determination between modeled ET(a) and measured ET(a) are in the range of 0.45-0.95, and root mean square errors are in the range of 10-30% of mean ET(a) values across biomes, similar to methods that use thermal infrared bands to estimate ET(a) and within the range of accuracy of the ground measurements by which they are calibrated or validated. The advent of frequent-return satellites such as Terra and planed replacement platforms, and the increasing number of moisture and carbon flux tower sites over the globe, have made these methods feasible. Examples of operational algorithms for ET in agricultural and natural ecosystems are presented. The goal of the review is to enable potential end-users from different disciplines to adapt these methods to new applications that require spatially-distributed ET estimates.
ISI Document Delivery No.: 681LY Times Cited: 7 Cited Reference Count: 112 Glenn, Edward P. Nagler, Pamela L. Huete, Alfredo R. Springer Dordrecht
Keywords: NDVI; Enhanced Vegetation Index; Fluxnet; MODIS; Remote sensing; land-surface evaporation; basal crop coefficients; colorado river delta; modis satellite data; canopy reflectance; potential evapotranspiration; riparian evapotranspiration; meteorological data; eddy covariance; energy-balance

The IndexDatabase - Henrich, V.; Krauss, G.; Götze, C.; Sandow, C. (2011)